Circ_0072464 Shuttled by Bone Mesenchymal Stem Cell-Secreted Extracellular Vesicles Inhibits Nucleus Pulposus Cell Ferroptosis to Relieve Intervertebral Disc Degeneration. (29th June 2022) - Yu, Xiaojun; Xu, Haoran; Liu, Qikun; Wang, Yingguang; Wang, Shanxi; Lu, Rui; Jiang, Yongqiao; Kang, Hao; Hu, Weihua
Abstract : Ferroptosis, as an iron-dependent form of necrotic cell death, has been reported to affect activities of nucleus pulposus cells (NPCs). However, its role in the pathogenesis of intervertebral disc degeneration (IDD) is largely unknown. Notably, our bioinformatics analysis predicted that circ_0072464 was downregulated in nucleus pulposus of IDD mice. Therefore, this study is aimed at clarifying the mechanisms of extracellular vesicle- (EV-) encapsulated circ_0072464 derived from bone marrow mesenchymal stem cells (BMSCs) in NPC ferroptosis in IDD. EVs were extracted from mouse BMSCs (BMSC-EVs) and then cocultured with IL-1 β -induced NPCs, followed by detection of matrix synthesis, proliferation, and ferroptosis of NPCs based on gain- or loss-of-function experiments. It was found that the uptake of BMSC-EVs by NPCs alleviated IDD. circ_0072464 and NRF2 were downregulated, and miR-431 was upregulated in IDD. Mechanistically, circ_0072464 competitively bound to miR-431, which targeted and inhibited NRF2 expression. BMSC-derived EVs carrying circ_0072464 inhibited NPC ferroptosis to promote matrix synthesis and proliferation of NPCs by inhibiting miR-431 and upregulating NRF2. Besides, in vivo experiments also confirmed that BMSC-EVs alleviated intervertebral disc lesions in mice with IDD through the circ_0072464/miR-431/NRF2 axis. Collectively, BMSC-EV-loaded circ_0072464 inhibited NPC ferroptosis to relieve IDD via upregulation of miR-431-mediated NRF2, therefore providing a potential therapeutic target against IDD.